Memory and Cerebral Blood Flow in Cases of Transient Global Amnesia During and After the Attack - H. Kazui; H. Tanabe; M. Ikeda; Y. Nakagawa; J. Shiraishi; K. Hashikawa (Behavioural Neurology)
We administered various memory tests and neuroimaging examinations to four pure cases who met Hodges' clinical criteria for transient global amnesia (TGA), during and after the attack. The purpose of the present study was to determine whether procedural learning is acquired during TGA and whether priming effects are preserved during TGA, and to investigate the anatomical basis of various memory subcomponents through these cases. Episodic memory was severely disturbed only during TGA, consistent with previous studies. Procedural learning during TGA examined by a drawing skill test and a reading skill test developed by us, and the Tower of Toronto, was preserved during TGA, consistent with one earlier report dealing with procedural memory during TGA. Priming effects during TGA have never been assessed. A word completion priming task with Kanji letters developed by us demonstrated that priming effects were preserved during TGA. Neuroradiologically, single photon emission computed tomograph hippocampal images clearly revealed a hypoperfusion confined to the medial portion of the bilateral temporal lobe only during the attack. These findings indicate that the medial portion of the temporal lobe is important for episodic memory as described in previous reports, but did not play an important role in procedural memory and priming effects.